Overcoming Investor Biases: The Role of Machine Learning in Financial Decision-Making - Haikarainen, Veera (My University, 2026)
Traditional financial models assume investors act as rational agents. However, behavioral finance demonstrates that investors are frequently influenced by cognitive biases in decision-making processes. The application of machine learning (ML) in behavioral finance provides an innovative and efficient way of analyzing market dynamics and investor behavior. The main objective of this thesis is to bridge the gap between traditional behavioral finance theories and the integration of ML models through a comprehensive literature review. The thesis builds on the theories of the Efficient Market Hypothesis and Prospect Theory to further discuss the relationship between market dynamics and cognitive anomalies. Machine learning algorithms offer solutions that enable the processing and evaluation of large datasets at a significantly faster pace than traditional human analysis alone. The findings of this thesis suggest that these predictive models can accurately detect and group investor behaviors, forecasting how these biases may influence individual actions and future market trends, such as increased volatility and asset mispricing. The findings highlight the practical integration of ML models into the finance industry by utilizing a hybrid human-AI decision model to enhance efficient and rational investment decision-making. By combining traditional statistics and ML models, this thesis aims to contribute to more effective decision-making while also highlighting the potential gaps and transparency issues within the finance industry.

Perinteiset rahoitusteoriat olettavat sijoittajien toimivan rationaalisesti. Käyttäytymistaloustiede kuitenkin osoittaa, että kognitiiviset harhat vaikuttavat usein sijoittajien päätöksentekoprosesseihin. Koneoppimisen soveltaminen käyttäytymistaloustieteessä tarjoaa puolestaan innovatiivisen ja tehokkaan tavan analysoida markkinadynamiikkaa ja sijoittajien käyttäytymistä. Tämän tutkielman päätavoitteena on tuoda perinteistä käyttäytymistaloustiedettä ja koneoppimismalleja tieteenaloina lähemmäksi toisiaan kirjallisuuskatsauksen avulla. Tutkielman teoriaosuus pohjautuu pääosiltaan tehokkaiden markkinoiden hypoteesiin ja prospektiteoriaan, joiden avulla käsitellään tarkemmin markkinadynamiikan ja kognitiivisten anomalioiden välistä suhdetta. Koneoppimisalgoritmit tarjoavat ratkaisuja, jotka mahdollistavat suurten tietoaineistojen käsittelyn ja arvioinnin huomattavasti nopeammin verrattuna perinteisen tilastotieteen tekemään analyysiin. Tämän tutkielman tulokset osoittavat, että koneoppimismallit pystyvät tarkasti havaitsemaan ja ryhmittelemään sijoittajien käyttäytymistä sekä ennakoimaan, kuinka kognitiiviset harhat voivat vaikuttaa yksittäisiin sijoittajiin sekä markkinatrendeihin, kuten varallisuuserien virheelliseen hinnoitteluun ja lisääntyneeseen volatiliteettiin. Tulokset kannustavat koneoppimismallien integroimista rahoitusalalle rajapinnaksi ihmisen ja tekoälyn välille hybridipäätöksentekomallin muodossa. Tämä tutkielma pyrkii edistämään tehokkaampaa päätöksentekoa ja tuomaan esiin rahoitusalan mahdollisia puutteita sekä läpinäkyvyysongelmia yhdistämällä perinteistä tilastotiedettä sekä koneoppimismalleja.
Keywords: machine learning; decision making; cognitive biases; artificial intelligence; investments (economics); fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|